Off the grid : histories of Belgian graphic design - De Bondt, Sara (S.l. : Occasional papers, 2022)
This book offers a collaborative panorama of Belgian graphic design history from a multiplicity of perspectives, with essays on type design, colonisation and labour relations among other subjects. Contributors include historians, practicing designers, teachers and first-hand accounts. With hundreds of previously unpublished illustrations such as posters, signage, typography, book design, logos and archival photographs. -- Interviews with Sophie Alouf-Bertot, Rob Buytaert, Boudewijn Delaere, Paul Ibou, and Herman Lampaert. Essays by Jo De Baerdemaeker, Pia Jacques and Leroy Meyer (Belgian Institute Graphic Design), Sara De Bondt, Jan Ceuleers, Katrien Van Haute, Richard Hollis, Jean-Michel Meyers, Hilde Pauwels, Hugo Puttaert, and Katarina Serulus.
Keywords: Graphic design (Typography) -- History -- 20th century -- Belgium